Ziconotide: a clinical update and pharmacologic review. (May 2013) - Pope, Jason E; Deer, Timothy R
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Ziconotide&logicalOpe1=OR&field2=articletitle&text2=Ziconotide&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Ziconotide is an N-type calcium channel antagonist to treat chronic pain that is delivered intrathecally. It is the only intrathecal, FDA-approved, non-opioid analgesic and is recommended as first-line therapy. Despite these advantages, a small therapeutic window limits ziconotide's clinical utility, with adverse event (AE) challenges that include, but are not limited to, dizziness, nausea, and somulence. Areas covered: Pharmacokinetics, pharmacodynamics, efficacy, safety, trialing, and chronic infusion after searching EMBASE, PubMed, and Cochrane Database of Systemic Reviews were used to search published literature from 1966 to January 1, 2013 to identify studies related to the intrathecal delivery of ziconotide. Expert opinion: Ziconotide is a safe and effective strategy to treat chronic pain, although limitations remain, including a small therapeutic window. Low starting doses and slow incremental increases and long titration intervals may improve tolerability. AEs may be mitigated by also employing combination therapy, although further study is needed. Concomitant use of ziconotide and morphine is an option when considering use of FDA-labeled intrathecal drugs in those resistant to monotherapy.